Bee pollination and association of apricot varieties - Szabó, Z.; Nyéki, J.; Benedek, P.; Erdős, Z.; Soltész, M. (International Journal of Horticultural Science, 2000)
Apricot yields are highly variable according to the season. The variation is caused mainly by the adversities during the critical processes of floral biology, i.e. blooming and fertilisation. On the basis of information concerning blooming time and mutual compatibility relations of apricot varieties a system of securing regular and adequate yields has been developed.Winter frosts of the continental type are well tolerated by most of the apricots, however, after the end of rest period, flower buds are loosing frost tolerance, 'rapidly.Being one of the fruit species blooming earliest during the early spring, apricot start to bloom in Hungary around the end of March or early April as a mean of many years, but it also happened, exceptionally that apricot started to bloom at February 20 (at Letenye South Hungary). The early season, exposes the floral organs to frost injuries. As a consequence, apricot orchards on the Great Plain produce low yields in 3 years, intermediate yields in other 3 years out of a ten-year-period.Moreover, weather conditions during the blooming period are often unfavourable for pollination. Cool, windy and rainy weather prevents the flight of insects and on the other hand, warm spells shorten the blooming process, nectarines and stigmata get dry and the female gametes loose viability before effective pollination occurres.The fertility of individual cultivars are meeting different obstacles. Apricot cultivars differ greatly in the rate of flowers bearing underdeveloped pistils, which may attain even 60% (e.g. Orangered). New commercial cultivars are often self-incompatible. Local varieties of that type in Hungary are the „óriás" varieties (e.g. Ceglédi óriás, Szegedi mammut), and the new hybrid Ceglédi Piroska. Many of the cultivars are variable in their self-fertility (partially self-fertile): Budapest, Harmat, Korai piros, Mandulakajszi.Inter-incompatibility is also known in apricots. The „óriás " varieties do not fertilise each other. During the growth of fruits, cool spells (2-4 °C) caused severe fruit shed in Ceglédi óriás.Apricot flowers produce pollen and nectar at average rates related to other fruit species, thus bees are attracted sufficiently. Bee visits are very variable according to growing site and season. Most of the bees are pollen gatherers but sometimes nectar suckers are in majority. Bee pollination is necessary not only for the self-incompatible varieties but also to enhance the yield of self-fertile varieties.Taking the blooming and fertility relations of the cultivars into account, plantations should not exceed two rows to a particular self-incompatible varieties, and possibly two different polliniser varieties are suggested to be planted as flanking the block in question.In commercial plantations 2 to 4 bee colonies per hectare are proposed to move for the whole blooming period.